Change in perioperative neutrophil-lymphocyte ratio as a potential predictive biomarker for chronic postsurgical pain and quality of life: an ambispective observational cohort study - Shu, Bin; Xu, Fang; Zheng, Xuemei; Zhang, Yamei; Liu, Qi; Li, Shiqi; Chen, Jie; Chen, Yuanjing; Huang, He; Duan, Guangyou (Frontiers in Immunology, 2023)
Introduction: Accurate and accessible predictors of chronic postsurgical pain (CPSP) to identify high-risk postsurgical patients are prerequisite for preventive and interventional strategies. We investigated the incidence and risk factors of CPSP after abdominal surgery, with a focus on plasma immunological markers. Materials and methods: This was a retrospective analysis of patients who underwent abdominal surgery under general anesthesia at a tertiary center between January 2021 and January 2022. The preoperative demographics, laboratory test data, and surgical factors of the participants were collected from the electronic medical record system. Postoperative pain intensity and living conditions 1 year after discharge from the hospital were assessed via a phone survey. Univariate and multivariate analyses were used to explore independent risk factors associated with CPSP. Results: A total of 968 patients were included, and 13.53% (n = 131 of 968) of patients reported CPSP 1 year after surgery. Patients with older age, open surgery, higher American Association of Anesthesiologists classification, patient-controlled intravenous analgesia application, longer surgery duration, higher postoperative absolute neutrophil count, and neutrophil-lymphocyte ratio (NLR), lower postoperative absolute lymphocyte count, and higher white blood cell count, were more likely to suffer from CPSP. A changed ratio of NLR (postoperative to preoperative) ≥ 5 significantly correlated with CPSP, moderate to severe pain, maximum numeric rating score since discharge from the hospital, and affected the quality of life. Discussion: The changed ratio of NLR could be used for the early identification of patients at risk for CPSP and affect the quality of life to alert the clinician to undertake further assessment.